Feeding behavior and mobility of carabid beetles in response to perceived risk of predation - Stefanie E. DE HEIJ; Khaldoun A. ALI; Sean M. PRAGER; Christian J. WILLENBORG (European Journal of Entomology, 2023)
Carabid beetles are common inhabitants of agricultural fields where they encounter a variety of food options - including prey and weed seeds. The feeding behaviors of carabids are often influenced by the physical and chemical traits of prey and seed species, as such traits determine prey or seed species that are suitable for consumption. However, some carabid species may prey upon other carabids, complicating their role as beneficial insects due to consumptive (direct) and non-consumptive (indirect) intra-guild predation effects. The non-consumptive effects of intra-guild predation are expected to influence prey and seed foraging behaviors of carabids because those behaviors are likely to be adapted as a function of duration and intensity of predation risk. In this study, we wanted to explore the non-consumptive effects of the carabid intra-guild predator Pterosticus melanarius on mobility and feeding behavior of two carabid omnivores: Harpalus amputatus and Amara spp. Choice and no-choice feeding arenas coupled with a video system were used to study the responses of carabid beetles to the odor cues of P. melanarius. Odor cues left by P. melanarius caused H. amputatus to reduce its activity when canola seeds (Brassica napus) were offered in the feeding arenas. In contrast, P. melanarius cues did not cause H. amputatus to alter its mobility when freeze-killed fruit flies were offered in the feeding arenas, although this species did increase consumption of fruit flies under these cues. Amara spp. offered canola seeds increased their mobility and relative seed preferences when exposed to the odor cues of P. melanarius. Overall, our work shows carabid species do alter aspects of their foraging behavior under intra-guild predation risks, but this is unlikely to reduce their contributions to seed or prey biocontrol.